Towards phase-based defect detection: A feasibility study in vibrating panels. (27th October 2022) - Cosco, F.; Cuenca, J.; Desmet, W.; Janssens, K.; Mundo, D.
Abstract: This work discusses the possibility of using phase-based motion magnification as a non-destructive inspection tool for defect detection and identification in vibrating panels. Phase-based motion magnification has recently emerged as a potentially disruptive technology in the field of optical methods for vibration engineering. In fact, the method allows to post-process high-speed video recordings in order to magnify small motions happening in a prescribed bandwidth. In particular, our strategy relies on measuring the full-field low-frequency eigen-shapes, and extracting their aberration as resulting from small defects. Effects of defects are usually very localized in space but may appear even at lower frequencies, making the approach particularly suitable for any kind of high-resolution full-field optical technique. Within this work, a novel phase-based processing pipeline for defect detection is described, and a set of preliminary tests is discussed to assess the feasibility and advantages of the methodology. All validations were carried out by means of numerical simulations relying upon a photo-realistic dynamic finite element model of a rectangular plate.